Jakość życia chorych z niewydolnością serca = Quality of life in patients with heart failure - Beata Kowalczyk; Rafał Czyż; Bożena Kaźmierska; Beata Jankowska-Polańska (Kazimierz Wielki University, 2016)
Kowalczyk Beata, Czyż Rafał, Kaźmierska Bożena, Jankowska-Polańska Beata. Jakość życia chorych z niewydolnością serca = Quality of life in patients with heart failure. Journal of Education, Health and Sport. 2016;6(10):197-214. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.160831 http://ojs.ukw.edu.pl/index.php/johs/article/view/3935       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 02.10.2016. Accepted: 15.10.2016.       Jakość życia chorych z niewydolnością serca Quality of life in patients with heart failure   Beata Kowalczyk, Rafał Czyż, Bożena Kaźmierska, Beata Jankowska-Polańska   Katedra Medycyny Ratunkowej, Zakład Pielęgniarstwa Internistycznego, Uniwersytet Medyczny im. Piastów Śląskich we Wrocławiu     Streszczenie: Wprowadzenie Przewlekła niewydolność serca jest poważnym problemem klinicznym, społecznym i ekonomicznym. W ostatnich latach częstość występowania tej choroby stale rośnie i znacząco ogranicza funkcjonowanie pacjentów w aspekcie bio-psycho-społecznym, obniżając poziom jego jakości życia. Cel pracy Ocena jakości życia pacjentów z niewydolnością serca. Materiał i metody Badaniem objęto 105 pacjentów z niewydolnością serca. Do jego przeprowadzenia wykorzystano anonimową ankietę własnego autorstwa, kwestionariusza AIS oraz kwestionariusza NHP. Przeprowadzono analizę statystyczną. Wyniki Najliczniejszą grupę stanowiły osoby ze średnim poziomem akceptacji choroby (56,2%). Najwięcej ankietowanych znajdowało się w II klasie w skali NYHA (56,2%) i wykazywało średni i dobry (33 vs. 20 ) stopień akceptacji choroby. Analiza kwestionariusza NHP wykazała, iż w grupie pacjentów z dobrym poziomem akceptacji choroby poziom zaburzeń funkcji jest znacznie niższy niż w grupie pacjentów nie akceptujących chorobę (p<0,001). W grupie ankietowanych osób najbardziej zaburzona była energia życiowa (63,0 ± 42,2), a najmniej izolacja społeczna (20,0 ± 27,8). Wnioski Wyższy poziom jakości życia warunkuje lepszą akceptację choroby. Na stopień akceptacji choroby pacjentów wpływa: płeć, wiek, miejsce zamieszkania, stan cywilny, frakcja wyrzutowa lewej komory, klasa czynnościowa wg NYHA, konieczność wezwania pogotowia lub udania się na SOR, niektóre choroby współistniejące i wszystkie domeny jakości życia. Na akceptację choroby wpływają ujemnie ograniczenia ruchowe, wyobcowanie społeczne, reakcje emocjonalne i poziom energii.  Im niższa jakość życia tym niższy poziom akceptacji choroby. Słowa kluczowe: niewydolność serca, jakość życia, akceptacja choroby.           Abstract: Background Chronic heart failure is a serious clinical, social and economic problem.  In recent years, the incidence of the disease is growing steadily and significantly reduces the functioning of the patients in terms of bio-psycho-social, lowering its level of life quality. Objectives Evaluation of life quality of patients with heart failure. Material and methods The study included 105 patients with heart failure. To carry out the study used an anonymous questionnaire of his own authorship, questionnaire AIS and the questionnaire NHP. Statistical analysis was performed. Results The largest group were people with an average level of acceptance of the disease (56.2%). Most respondents were in class II of NYHA (56.2%), and showed the average and good (33 vs 20) degree of disease acceptance. Analysis of the questionnaire NHP showed that in patients with a good level of disease acceptance dysfunction is much lower than in the group of patients that don't accept the disease (p <0.001). In the group of respondents the most disturbed was the life energy (63.0 ± 42.2) and the least social isolation (20.0 ± 27.8). Conclusions A higher level of life quality determines a better acceptance of illness. The degree of disease acceptance depends on gender, age, place of residence, marital status, left ventricular ejection fraction of the heart, NYHA functional class, the need to call an ambulance or go to the emergency department, some comorbidities and all the domains of life quality. The lower of life quality, the lower level of disease acceptance is. Key words: heart failure, quality of life, illness acceptance.